2004
DOI: 10.1167/iovs.03-0687
|View full text |Cite
|
Sign up to set email alerts
|

Model of Endothelin-1–Induced Chronic Optic Neuropathy in Rat

Abstract: ET-1 led to a mean reduction in optic nerve blood flow of 68%. There were no significant differences in RGC survival among the four ET-1 doses used in this study. Pooled across all ET-1 doses, RGC survival decreased incrementally at 21, 42, and 84 days (P < 0.001; mean +/- SD, 0.77 +/- 0.25, 0.60 +/- 0.27, and 0.50 +/- 0.26, respectively) and was statistically significantly lower at each time point than in the BSS-treated animals. The axon survival data also showed a similar time-dependent loss. Only one of 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
1
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 40 publications
3
96
1
5
Order By: Relevance
“…They are potent vasoconstrictors and have been found to be elevated in the aqueous humor of glaucoma patients (Noske et al 1997;Tezel et al 1997). Intraocular administration of endothelin 1 leads to acute blockage of axonal transport Wang et al 2008b), optic neuropathy, and ganglion cell loss (Chauhan et al 2004;Sasaoka et al 2006). It was recently shown that endothelin 2, which binds to the same receptors as endothelin 1, also causes ganglion cell loss and optic nerve damage (Howell et al 2011).…”
Section: Differential Gene Expression In Glaucomamentioning
confidence: 99%
“…They are potent vasoconstrictors and have been found to be elevated in the aqueous humor of glaucoma patients (Noske et al 1997;Tezel et al 1997). Intraocular administration of endothelin 1 leads to acute blockage of axonal transport Wang et al 2008b), optic neuropathy, and ganglion cell loss (Chauhan et al 2004;Sasaoka et al 2006). It was recently shown that endothelin 2, which binds to the same receptors as endothelin 1, also causes ganglion cell loss and optic nerve damage (Howell et al 2011).…”
Section: Differential Gene Expression In Glaucomamentioning
confidence: 99%
“…The model of chronic optic nerve ischemia continuously delivers ET-1 to the perineural region of the optic nerve in the retrobulbar space and has been described in rabbits, 91 rats, 119 and nonhuman primates. 120 The arterial supply of the anterior optic nerve in the rabbit is anatomically similar to the primate eye and demonstrates a dose-dependent vasoconstriction with chronic, local application of ET-1.…”
Section: Rabbit Modelmentioning
confidence: 99%
“…Plasma and aqueous humor concentrations of ET-1 have been shown to be elevated in patients with ocular hypertension as well as in the corresponding animal models (49 -51). Chronic local administration of ET-1 to the optic nerve head reduces optic nerve head blood flow and is associated with a loss of retinal ganglion cells (52). In addition to these vascular effects, ET-1 is implicated in pathological changes in the retina such as neuronal cell apoptosis, microvascular basement membrane thickening, and gliosis (53).…”
Section: Endothelin-1 (Et-1)-receptor Antagonistsmentioning
confidence: 99%